Study of the survival of patients with head and neck cancer in relation to Circulating Tumor Cells (CTCs). - Romina Mastronicola; Elise Kayser; Pauline Le Roux; Agathe Barrat; Alexandre Aubertin; Aurore Casse; Léa Nominé; Hélèna Villard; Sophie Cortese; Emilie Beulque; Jean-Louis Merlin; Gilles Dolivet (PLoS ONE)
Distant metastasis in head and neck cancer are one of the first factors contributing to death. Currently, it is difficult to detect them early with our conventional techniques such as Positron Emission Tomography scanner (PET-scanner) and Magnetic Resonance Imaging (MRI). Therefore, it is important to find new markers that can help us in the care of the patient. This study aimed at comparing two methods (Reverse Transcription-Polymerase Chain Reaction and CellSearch) to detect circulating tumor cells (CTC) as a prognosticator. Results were statistically significant for markers EphB4 (p-value =  0.0003), CEA (p-value =  0.0006), CK 18 (p-value =  0.0011) and Ep-CAM (p-value =  0.0299) and demonstrate that our detection techniques could be used by optimizing our protocol. In addition, results of the rate of CTCs helped identify this as an indicator of a prognosis for the patient. Indeed, the study revealed that most patients in remission exhibited a decrease in post-operative CTCs, whereas patients experiencing relapses demonstrated an increase in CTCs, which was correlated with a poor prognosis.